Cardiovascular Risk Reduction in the Extreme Elderly. (March 2013) - Parikh, Seema; Sharkey, Kerith; Workman, Barbara
ABSTRACT: An American Heart Association statement on secondary prevention of coronary heart disease in the elderly reported that 50% of women and 70% to 80%) of men over 75 years have obstructive coronary artery disease. The total direct and indirect costs of cardiovascular disease and stroke in the US for 2007 was around 286 billion and annual costs are projected to rise to over 1 trillion by 2030. Significant emphasis is now placed on prevention and risk factor modification of cardiovascular disease. The proportion of the population aged 85 years and older (the 'extreme elderly') is projected to increase to 151% by 2030. This review focuses on reducing risk in coronary heart disease and congestive heart failure in the extreme elderly. We review modifiable cardiovascular risk factors (hypertension, lipid profile, lifestyle modification), pharmacological strategies (statins, beta‐blockers, angiotensin converting enzyme inhibitors, angiotensin II receptor blockers, aspirin) and the available evidence for their use in extreme old age. There is insufficient evidence to reach major conclusions with respect to cardiovascular risk reduction in the extreme elderly. Further trials involving older patients are needed before evidence‐based recommendations can be formulated for this population.